Multiple Targets for Oxysterols in Their Regulation of the Immune System - Lisa Reinmuth; Cheng-Chih Hsiao; Jörg Hamann; Mette Rosenkilde; John Mackrill (Cells, 2021)
Oxysterols, or cholesterol oxidation products, are naturally occurring lipids which regulate the physiology of cells, including those of the immune system. In contrast to effects that are mediated through nuclear receptors or by epigenetic mechanism, which take tens of minutes to occur, changes in the activities of cell-surface receptors caused by oxysterols can be extremely rapid, often taking place within subsecond timescales. Such cell-surface receptor effects of oxysterols allow for the regulation of fast cellular processes, such as motility, secretion and endocytosis. These cellular processes play critical roles in both the innate and adaptive immune systems. This review will survey the two broad classes of cell-surface receptors for oxysterols (G-protein coupled receptors (GPCRs) and ion channels), the mechanisms by which cholesterol oxidation products act on them, and their presence and functions in the different cell types of the immune system. Overall, this review will highlight the potential of oxysterols, synthetic derivatives and their receptors for physiological and therapeutic modulation of the immune system.